CROSS-SECTIONAL DIFFERENCES IN THE LEVEL OF DEPRESSION SINCE THE COVID-19 OUTBREAK: A STUDY ON SHARE DATA (Revista Inclusiones, 2021)
Depression is one of the most prevailing mental health problems nowadays and researchers expect it to deepen especially in most developed countries due to constantly aging population. At the same time the COVID-19 pandemic has led to overwhelming levels of distress by imposing severe restrictions on everyday activities of the world population. This situation inevitably created many stressful life events, and together with distancing measures, employment and financial insecurity, represent a massive mental health crisis. Moreover, according to SHARE data the changes in level of depression differ across Europe and while some countries such as Denmark and Slovenia exhibit comparatively low percentage of people stating that they feel sadder or depressed since the outbreak, other countries such as Portugal and Italy exhibit higher values of these indicators. Our paper aims to study the cross-sectional differences in the level of depression in the light of the additional risks that emerged since the COVID-19 outbreak for people in Europe and Israel. We base our analysis on the COVID-19 release of wave 8 of the SHARE project and we consider all the countries included in this wave. Based on extensive literature review we identify a set of variables associated with additional risks for the mental health since the outbreak. Then we apply factor analysis and extract risk factors that appeared due to the pandemic situation. As a next step we conduct K-means clustering over the identified factors so as to define distinct groups of respondents in terms of the effects caused by the pandemic situation and the lockdown measures. We profile each group by analyzing additional data for gender and age as well as changes in the level of depression. Last but not least, we summarize the proportion of respondents belonging to each cluster thus shedding light to the observed cross-sectional differences.